2011
DOI: 10.1002/chem.201100519
|View full text |Cite
|
Sign up to set email alerts
|

Substituent‐Controlled Reactivity in the Nazarov Cyclisation of Allenyl Vinyl Ketones

Abstract: Alkyl substitution α to the ketone of an allenyl vinyl ketone enhances Nazarov reactivity by inhibiting alternative pathways involving the allene moiety and through electron donation and/or steric hindrance. This substitution pattern also accelerates Nazarov cyclisation by increasing the population of the reactive conformer and by stabilising the oxyallyl cation intermediate. Furthermore, α substitution by an alkyl group does not alter the regioselectivity of interrupted Nazarov reactions when the oxyallyl cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
41
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(44 citation statements)
references
References 30 publications
3
41
0
Order By: Relevance
“…Under these conditions, the 1 H and 13 C{ 1 H} NMR spectra are again in accordance with a cyclopentene core, however both the 1 H and 13 C C(c)-CH3 resonances now exhibit coupling with the phosphorous atom; 2 JC-P and 3 JH-P couplings of 3.6 and 1.2 Hz, respectively. The 1 JC-P coupling of 65.9 Hz is now observed for the C(c) 13 C resonance at δ 78.9. For compound 3, attack of the phosphine moiety on the face opposite of the phenyl group is supported by the dipolar coupling between one of the P-CH3 groups and the proton on the carbon atom also bearing the phenyl group (see ESI).…”
mentioning
confidence: 79%
See 3 more Smart Citations
“…Under these conditions, the 1 H and 13 C{ 1 H} NMR spectra are again in accordance with a cyclopentene core, however both the 1 H and 13 C C(c)-CH3 resonances now exhibit coupling with the phosphorous atom; 2 JC-P and 3 JH-P couplings of 3.6 and 1.2 Hz, respectively. The 1 JC-P coupling of 65.9 Hz is now observed for the C(c) 13 C resonance at δ 78.9. For compound 3, attack of the phosphine moiety on the face opposite of the phenyl group is supported by the dipolar coupling between one of the P-CH3 groups and the proton on the carbon atom also bearing the phenyl group (see ESI).…”
mentioning
confidence: 79%
“…12 In a joint experimental and theoretical study, it was shown that the selectivity for nucleophilic addition at position (a) can be attributed to an electronic bias (the carbon at position (a) is a better electrophile) rather than steric effects (methyl group at position (c)). 13 Herein, we report not only that the Lewis acid alane moiety in ambiphilic compound (Me2PCH2AlMe2)2 efficiently initiates the Nazarov cyclization of AVK 2, but that the phosphine moiety can selectively trap the oxyallyl cation at 40 position (a) or (c), which to our knowledge is unprecedented. 14 (see ESI).…”
mentioning
confidence: 90%
See 2 more Smart Citations
“…The presence of α‐substituents facilitates the [3+4]‐cycloaddition of allenyl vinyl ketones 107 since the desired products 108a, b, d were isolated in high yields (Scheme ) . Unsubstituted substrates gave the [3+4]‐cycloaddition product 108c , but the Nazarov cyclization was not observed.…”
Section: Interrupted Nazarov‐type Reactionmentioning
confidence: 99%